2023
DOI: 10.1186/s40463-023-00629-6
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Women in Otolaryngology—Head and Neck Surgery part 1: The relationship of gender identity to career trajectory and experiences of harassment

Abstract: Introduction Women in surgical specialties face different challenges than their male peers. However, there is a paucity of literature exploring these challenges and their effects on a Canadian surgeon’s career. Methods A REDCap® survey was distributed to Canadian Otolaryngology–Head and Neck Surgery (OHNS) staff and residents in March 2021 using the national society listserv and social media. Questions examined practice patterns, leadership positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Specific to otolaryngology, a Canadian study revealed that female OTO‐HNS reported verbal and nonverbal sexual harassment more frequently compared with their male colleagues. 21 Pereira reported that females were underrepresented across all academic ranks in top‐rated U.S. otolaryngology programs, which unquestionably exacerbates these conditions. 6 These studies should motivate our medical community to invest in diversity initiatives and support the growing number of female physicians and surgeons worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to otolaryngology, a Canadian study revealed that female OTO‐HNS reported verbal and nonverbal sexual harassment more frequently compared with their male colleagues. 21 Pereira reported that females were underrepresented across all academic ranks in top‐rated U.S. otolaryngology programs, which unquestionably exacerbates these conditions. 6 These studies should motivate our medical community to invest in diversity initiatives and support the growing number of female physicians and surgeons worldwide.…”
Section: Discussionmentioning
confidence: 99%